2008
DOI: 10.1115/1.2812330
|View full text |Cite
|
Sign up to set email alerts
|

Periodical Unsteady Flow Within a Rotor Blade Row of an Axial Compressor—Part II: Wake-Tip Clearance Vortex Interaction

Abstract: In this two-part paper, results of the periodical unsteady flow field within the third rotor blade row of the four-stage Dresden low-speed research compressor are presented. The main part of the experimental investigations was performed using laser Doppler anemometry. Results of the flow field at several spanwise positions between midspan and rotor blade tip will be discussed. In addition, time-resolving pressure sensors at midspan of the rotor blades provide information about the unsteady profile pressure dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…This is probably due to the interaction between the upstream wake and tip leakage vortex. Analogous phenomenon were observed by Sirakov [21], Mailach [22] and Zhang [23], who drawed the same conclusion in the study. Figure 21 shows axial vorticity distribution on the cross section 85% C x downstream of rotor leading edge at time t ¼ T (only 0.5-1 span showed).…”
Section: Analysis Of Numerical Resultssupporting
confidence: 89%
“…This is probably due to the interaction between the upstream wake and tip leakage vortex. Analogous phenomenon were observed by Sirakov [21], Mailach [22] and Zhang [23], who drawed the same conclusion in the study. Figure 21 shows axial vorticity distribution on the cross section 85% C x downstream of rotor leading edge at time t ¼ T (only 0.5-1 span showed).…”
Section: Analysis Of Numerical Resultssupporting
confidence: 89%
“…It was found that strong interaction between upstream wake and rotor tip leakage vortex could lead to a performance benefit in the rotor tip region during the whole operability range of interest. The experimental result of Mailach et al (2008) revealed a strong periodical interaction of the incoming stator wakes and the compressor rotor blade tip clearance vortices. As a result of the wake influence, the tip clearance vortices are separated into different segments with higher and lower velocities and flow turning or subsequent counter-rotating vortex pairs.…”
Section: Unshrouded Tip Leakage Flow Interactionmentioning
confidence: 96%
“…To allow for studies of the periodically disturbed TLV seen by Mailach et al (2008) in the LSRC, the linear cascade setup was chosen to match the geometry and particularly reproduce the kinematics found in the rotating rig. Figure 3(a) shows the pitch averaged inlet conditions to the rotor blade row of the LSRC and the values adjusted in the wind tunnel.…”
Section: Definition Of Operating Pointmentioning
confidence: 99%
“…In the case of compressor rotors the main secondary flow phenomenon affected by the incoming wakes is the tip leakage vortex (TLV). As shown by Mailach et al (2008), incoming stator wakes trigger a cyclic segmentation of the TLV structure by interacting with its outer shear layer. Besides continuative experimental studies (e.g.…”
Section: Introductionmentioning
confidence: 99%